2016
DOI: 10.1089/omi.2016.0112
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Metabolomics After Natural Product Treatment in an Experimental Model of Cerebral Ischemia

Abstract: Cerebrospinal fluid (CSF) is an important biofluid for diagnosis of and research on neurological diseases. However, in-depth metabolomic profiling of CSF remains an analytical challenge due to the small volume of samples, particularly in small animal models. In this work, we report the application of a high-performance chemical isotope labeling (CIL) liquid chromatography-mass spectrometry (LC-MS) workflow for CSF metabolomics in Gastrodia elata and Uncaria rhynchophylla water extract (GUW)-treated experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For instance, differential 12 C-/ 13 C-dansylation labeling LC–MS has been shown to be a powerful method for analyzing amine- and phenol-containing metabolites or the amine/phenol submetabolome . Dansylation LC–MS has been applied to analyze many different types of biological samples, such as cells, plasma, cerebrospinal fluid, and fecal matter, with relatively high submetabolome coverage (i.e., thousands of metabolites). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, differential 12 C-/ 13 C-dansylation labeling LC–MS has been shown to be a powerful method for analyzing amine- and phenol-containing metabolites or the amine/phenol submetabolome . Dansylation LC–MS has been applied to analyze many different types of biological samples, such as cells, plasma, cerebrospinal fluid, and fecal matter, with relatively high submetabolome coverage (i.e., thousands of metabolites). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, consistent with the previous studies (28,29), we also found that glutamine, phenylalanine and tyrosine levels were increased significantly in MB patients (Table 3). Gamma-aminobutyric acid (GABA), an inhibitory neurotransmitter, derived from glutamate was also observed to be enhanced and its increase could be explained as a potential protective change in response to the excitatory neurotoxicity (30). Interestingly, we found that glutamate levels in IS patients were not altered compared to control in the current study, which was in 10.3389/fneur.2023.1153193…”
Section: Discussionmentioning
confidence: 42%
“…One study [ 37 ] evaluated a macaque model of CSF. The remaining four studies [ 38 , 39 , 40 , 41 ] evaluated a rat model of ischemic stroke. All rat model studies evaluated the progression of ischemic stroke, which was defined as worsening of neurological symptoms in the early course of stroke presentation [ 42 ].…”
Section: Resultsmentioning
confidence: 99%